Determination of Coxiella burnetii in bovine foetuses using PCR and immunohistochemistry - Ozkaraca, M.; Ceribasi, S.; Ceribasi, A. O.; Kilic, A.; Altun, S.; Comakli, S.; Ongor, H. (Czech Academy Agricultural Sciences, 2016)
This study was aimed at detection of Coxiella burnetii in bovine foetuses using polymerase chain reaction (PCR) and immunohistochemistry (IHC) and at an estimation of its frequency in Eastern Turkey. Stamp, Giemsa, and Gimenez stains were used in addition to PCR and IHC to determine the presence of C. burnetii in samples from 70 bovine foetuses. While the staining methods did not detect the agent by direct visualisation of C. burnetii on smears, PCR and IHC identified its presence in two of the foetuses. The distribution of antigens in these two foetuses was, in decreasing order of concentration, in the spleen, the thymus, the lungs, the liver, and the kidneys. We conclude that C. burnetii diagnosis in bovine foetuses can be reliably performed using PCR and IHC. In addition, the frequency of 1.42% of C. burnetii positivity in bovine foetuses reported here was the first time that the presence of this agent was determined in Eastern Turkey.
Keywords: Q fever; diagnostic method; IHC; cow; Eastern Turkey